A new facility for high-energy neutron-induced fission studies - A. Prokofiev (2018)
A new facility is constructed for measurements of neutron-induced fission cross sections in the 20-180 MeV energy region versus the np scattering cross section, which is adopted as the primary neutron standard. The advantage of the experiment compared to earlier studies is that the fission-fragment detection and the neutron-flux measurement via np scattering are performed simultaneously and at the same position in the beam, and, therefore, many sources of systematic errors cancel out. Further reduction of systematic errors is achieved due to "embedded" determination of effective solid angle of particle detectors using α-particles from the radioactive decay of the target nuclei. The performance of the facility is illustrated by first data obtained for angular distributions of fission fragments in the238U(n,f) reaction. © 2005 American Institute of Physics.